Modelling SOI PIN Diode for Energy Harvesting Application - Mohd Anuar, Ainul Nazhan; Mat Jubadi, Warsuzarina (Evolution in Electrical and Electronic Engineering, 2023)
A photodiode model which able to harvest energy in standard PIN photodiode design processes is presented, output current of most photodiodes in an open circuit is low and worsens the parasitic diode effect. The purpose of using this photodiode design is to evaluate current and voltage performance. The photodiode was designed and simulated in COMSOL Multiphysics by using silicon material with varying thicknesses. High current output, wider intrinsic layer, and value of breakdown voltage were achieved by varying the thickness. This photodiode current output is 9μA when the thickness is 1μm and the percentage of current increment is between 6% and 18%. The width of the intrinsic layer increase by 10% and the breakdown voltage also increases in proportion to the width of the intrinsic layer. Finally, from the studies, the current, width of the intrinsic layer, and breakdown voltage increase when the thickness of the model increase.